Prawda, prowokacja, propaganda. Obrazy Holocaustu w internetowych serwisach plików wideo - Otto, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
Truth, provocation, propaganda. Images of the Holocaust in the Web services The word “Holocaust” functions as a keyword in reading of the contemporary history in the Web services (which contain video files). Very often this word is used in the context of some historical truth which concerns the second world war. There are mainly some newsreels or audiovisual documents which confirm the atrocities of the war. The forms of the provocation are rather rarely. In this perspective the authors want to notice some peculiar problems or phenomenona. Sometimes the word “Holocaust” is used by some communities to support their ideologies (for example in the political background) – and in this context the interpretation of this word exceeds the ethical taboo.